2016
DOI: 10.5206/eei.v26i1.7734
|View full text |Cite
|
Sign up to set email alerts
|

Structured Intervention as a Tool to Shift Views of Parent–Professional Partnerships: Impact on Attitudes Toward the IEP

Abstract: The Individualized Education Program (IEP) is the roadmap that helps educators and families drive the education of students with disabilities, improve outcomes, and fulfill each child’s potential. However, the IEP can be challenging due to the large number and diversity of stakeholders, dynamics and culture of collaboration, and the complex procedures guiding the referral, evaluation, and placement. This study describes changes in attitudes toward the IEP reported by special educators and parents participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…When the literature was examined, it was found that the experiences of parents of individuals with special needs regarding IEP meetings were examined (Fish, 2008;Kirksey et al, 2022;Macleod et al, 2017;Zeitlin & Curcic, 2010), parent-expert cooperation in the IEP development process was discussed (Broomhead, 2013;Mereoiu, et al 2016;Murray, 2000;O'Connor, 2008), studies on the role of stakeholders in the IEP team in the IEP development process (Eratay et al, 2012;Gilliam & Coleman, 1981), and a study examining how the process works in IEP meetings attended by students with special needs (Royer, 2017). In addition, school administrators and classroom teachers (Çuhadar, 2006), Guidance Research Center (GRC) staff and special education teachers (Avcıoğlu, 2011;Öztürk & Eratay, 2010;Bafra Tike & Kargın, 2009), the difficulties faced by school administrators regarding the IEP development process and their suggestions for solutions (Yaman, 2017;Yılmaz, 2013), and the experiences and difficulties experienced by teachers (Akcin, 2022;Kozikoğlu & Albayrak, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the literature was examined, it was found that the experiences of parents of individuals with special needs regarding IEP meetings were examined (Fish, 2008;Kirksey et al, 2022;Macleod et al, 2017;Zeitlin & Curcic, 2010), parent-expert cooperation in the IEP development process was discussed (Broomhead, 2013;Mereoiu, et al 2016;Murray, 2000;O'Connor, 2008), studies on the role of stakeholders in the IEP team in the IEP development process (Eratay et al, 2012;Gilliam & Coleman, 1981), and a study examining how the process works in IEP meetings attended by students with special needs (Royer, 2017). In addition, school administrators and classroom teachers (Çuhadar, 2006), Guidance Research Center (GRC) staff and special education teachers (Avcıoğlu, 2011;Öztürk & Eratay, 2010;Bafra Tike & Kargın, 2009), the difficulties faced by school administrators regarding the IEP development process and their suggestions for solutions (Yaman, 2017;Yılmaz, 2013), and the experiences and difficulties experienced by teachers (Akcin, 2022;Kozikoğlu & Albayrak, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies show that teachers and school administrators encounter certain difficulties during the IEP process including limited teacher and parent participation as well as lack of collaboration among team members, professional development opportunities and support services (Fish, 2008;Johns, Crowley, & Guetzloe, 2002;Kreutzer, 2004;Lee-Tarver, 2006;Lo, 2014;Lytle & Bordin, 2001;Menlove, Hudson, & Suter, 2001;Mereoiu, Abercrombie, & Murray, 2016;Minke, Bear, Deemer & Griffin, 1996;Salas, 2004;Sanches-Ferreira, Lopes-dos-Santos, Alves, Santos, & Silveira-Maia, 2013;Timothy & Agbenyega, 2018;Zeitlin & Curcic, 2014). The national literature generally supports these findings in terms of limited family involvement, special education support services and professional development opportunities (Akalın 2014;Ateş, 2017;Avcıoğlu, 2011Avcıoğlu, , 2012Berkant & Atılgan, 2017;Can, 2015;Coşkun, 2010;Debbağ, 2017;Ersan & Ata, 2017;İlik & Sarı, 2017;Kuru-Habiboğlu, 2018;Kuyumcu, 2011;Öztürk & Eratay, 2010;Rakap, 2015;Söğüt & Deniz, 2018;Şahin & Gürler, 2018;Tike-Bafra & Kargın, 2009;Yaman, 2017;Yener, 2019;Yılmaz & Batu, 2016).…”
Section: Tartışma Ve Sonuçmentioning
confidence: 99%
“…Yurt dışı alanyazda, BEP sürecinin öğretmen görüşlerine göre değerlendirildiği çok sayıda araştırma dikkati çekmekte ve bu araştırmalar genel olarak; öğretmen ve okul yöneticilerinin BEP sürecinde birtakım olumsuzluklarla karşılaştıkları, eğitimciler ve ailelerin BEP sürecine sınırlı katılım gösterdikleri, işbirliğinde zorlandıkları ve okul personelinin mesleki gelişim etkinlikleri ile destek hizmetlere gereksinim duydukları yönünde sonuçlar ortaya koymaktadır (Fish, 2008;Johns, Crowley, & Guetzloe, 2002;Kreutzer, 2004;Lee-Tarver, 2006;Lo, 2014;Lytle & Bordin, 2001;Menlove, Hudson, & Suter, 2001;Mereoiu, Abercrombie, & Murray, 2016;Minke, Bear, Deemer, & Griffin, 1996;Salas, 2004;Sanches-Ferreira, Lopes-dos-Santos, Alves, Santos, & Silveira-Maia, 2013;Timothy & Agbenyega, 2018;Zeitlin & Curcic, 2014). Bu sonuçlar, gelişmiş ülkelerde dahi BEP'e ilişkin sorunların günümüzde de süregidiyor olduğunu gözler önüne sermektedir.…”
unclassified
“…Dans le cas où les parents ne parlent pas la langue de scolarisation, l'interprète doit traduire de façon adéquate afin qu'une bonne compréhension en découle (Hart et coll., 2012 la collaboration (Buckley, 2005;Friend, 2000;Hartmann, 2016). Aussi, le besoin de formation des enseignants à cet égard (Gallagher et Odozi, 2010;Goepel, 2009;Idol, 2006;Mereoiu, 2016;Paulsen, 2008;Wilson, 2015) et leur manque de connaissances au sujet des situations que vivent les élèves (Buckley, 2005;McCord et Watt, 2010) ressortent de façon récurrente des écrits recensés plus haut. Cette récurrence fait écho aux recommandations de Rousseau et coll.…”
Section: Acteurs Oeuvrant Au Sein De Divers Périmètresunclassified
“…Le recours aux formules et aux tests sème la confusion chez les parents, et les difficultés de ces derniers à comprendre tous les tenants et les aboutissants du processus légitiment en quelque sorte l'école à prendre des décisions sans tenir compte de leur avis. Par exemple, ces auteurs rapportent que le recours aux menus déroulants composés de rubriques fixes (par exemple, « habiletés à la communication ») dans le gabarit du plan ne permet pas d'inclure le discours et les nuances qu'apportent les parents Mereoiu, Abercrombie et Murray (2016). abondent dans le même sens quand ils précisent que ces 'une personne-ressource ou tierce atténue les rapports de pouvoir, précisent ces auteurs, mais le personnel de l'école aurait alors tendance à s'adresser plutôt à cette personne qu'aux parents, ce qui perpétue voire accentue leur position minoritaire dans le processus.…”
unclassified